A compact and cost effective quasi-in-situ method to characterize broadband RF shielding effectiveness of materials for advanced microelectronic packaging. (November 2022) - Miao, Min; Zhang, Danya; Nie, Xin; Bu, Jingpeng
Abstract: At present, one of the major measures to suppress electromagnetic (EM) radiation inside advanced integrated microelectronic packages is the proper placement of electromagnetic shielding. Existing shielding effectiveness (SE) characterization technologies are always intended for enclosure evaluation, which are costly and time consuming, demanding complicated test instrument configuration, fixture setup, and a large room to accommodate the whole test system, especially when broadband test is required in which a series of narrowband antennas are to be switched during the test; additionally, the way test samples are assembled is quite different from that in the final package application. Therefore, their practical value and adaptation in SE evaluation are limited in the view of the professionals engaged in micro/nano electronics package research, development, manufacturing and application, and indeed there exist urgent desires for a compact and cost-effective technology characterizing in-situ the broadband effectiveness of shielding materials for EM radiation suppression in high-density heterogeneously integrated packages and relevant miniaturized system integration scenarios. Accordingly, in this paper a compact dual-port microstrip antenna test fixture working in pairs is designed and prototyped, which provides a quasi in-situ environment for the test sample, and only a vector network analyzer (VNA) is needed which just measures the fixture port scattering parameters so as to conveniently and faithfully reveal the SE. Solid modeling and full-wave simulation for the broadband return loss, insertion loss and radiation pattern of the test setup are carried out by a high-frequency electromagnetic structural analysis software for design verification. The actual test is carried out by loading heat insulation board, heat insulation board laminated with aluminum foil, PureBlue board and FR4 board samples. By comparing the SE of different materials, the validity for the proposed microstrip antenna test fixture in characterization is confirmed.